Antecedents, outcomes, and mediating role of internal reference prices in pay-what-you-want (PWYW) pricing - Roy, Rajat; Rabbanee, Fazlul; Sharma, Piyush (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to explore the mediating role of internal reference price (IRP) in a pay-what-you-want (PWYW) price setting. Specifically, it examines the effects of altruism, social desirability and price consciousness as the antecedents of IRP and consumers’ willingness to pay (WTP), future purchase intention and attitude toward the seller as the outcomes of IRP. Design/methodology/approach – The data for the study were collected from 272 respondents through a structured survey and analyzed through structural equation modeling technique using AMOS 22.0. Findings – Altruism and social desirability positively influence IRP whereas price consciousness influences IRP negatively. IRP mediates the effects of altruism, social desirability and price consciousness on WTP, future purchase intention and attitude toward the seller. Research limitations/implications – PWYW pricing strategy can help attract consumers with self-less characteristics or a desire to behave in a socially appropriate manner but not those who are highly price conscious as reflected by the differences in the way in which their IRPs influence their WTP, future purchase intention and attitude toward the seller. Originality/value – This paper introduces a parsimonious framework to explain how three consumer characteristics influence consumers’ pricing decisions in PWYW context. The finding that the effects of antecedent variables on WTP, attitude and future purchase intention are mediated by IRP provides new insights that have not been explored earlier.